(untitled) (Confluenţe Bibliologice, 2026)
This article examines the Mihai Eminescu Monument in Galați, the country’s first statue dedicated to the poet, highlighting its historical context, Frederic Storck’s artistic work, and its symbolic role in the city’s cultural life. The study also notes the poet’s connection to Galați and the monument’s successive relocations.